2019
DOI: 10.1002/yea.3381
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation by organic nitrogen of AOX1 promoter used for controlled expression of foreign genes in the yeast Pichia pastoris

Abstract: Pichia pastoris is a well-established cell factory for recombinant protein synthesis. Various optimization strategies of processes based on AOX1 promoter have been investigated, including methanol co-feeding with glycerol or sorbitol during the induction stage. Compared with carbon sources, comparatively little research has been devoted to the effects of nitrogen sources. Several reports have described the benefits of adding casamino acids (CA) to the recombinant protein production medium, however, without con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In Pichia pastoris, it has been shown that the choice of N source can regulate the activity of genes involved in methanol assimilation (Rumjantsev et al, 2014). For example, the activity of the AOX1 promoter in P. pastoris was reported to be reduced in the presence of free amino acids in the cultivation medium (Velastegui et al, 2019). The expression of the LDH in this study is regulated by the MOX promoter, which is O. polymorpha's native homolog to the AOX1 promoter.…”
Section: Discussionmentioning
confidence: 59%
“…In Pichia pastoris, it has been shown that the choice of N source can regulate the activity of genes involved in methanol assimilation (Rumjantsev et al, 2014). For example, the activity of the AOX1 promoter in P. pastoris was reported to be reduced in the presence of free amino acids in the cultivation medium (Velastegui et al, 2019). The expression of the LDH in this study is regulated by the MOX promoter, which is O. polymorpha's native homolog to the AOX1 promoter.…”
Section: Discussionmentioning
confidence: 59%
“…Specifically, addition of proline, glutamic acid, and casamino acids was reported to downregulate expression from the commonly used AOX1 promoter. 31,32 This indicates that intracellular amino acid concentrations may also trigger several other metabolic processes within a cell which influence protein synthesis. Our metabolomics data could display a direct impact of recombinant protein production on intracellular amino acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Most amino acids are known as rather poor nitrogen sources and thus supplementation may have a negative influence on protein synthesis. Specifically, addition of proline, glutamic acid, and casamino acids was reported to downregulate expression from the commonly used AOX1 promoter 31,32 . This indicates that intracellular amino acid concentrations may also trigger several other metabolic processes within a cell which influence protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Beside this, nitrogen sources such as casamino acid have also been reported to regulate methanol metabolism (Velastegui et al . 2019 ). Indeed, expression of the genes AOX1 , DAS1 and FLD1 is reduced in the presence of 0.1% of casamino acid.…”
Section: Nitrogen Metabolismmentioning
confidence: 99%